2019
DOI: 10.1183/13993003.00786-2018
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils disturb pulmonary microcirculation in sepsis-induced acute lung injury

Abstract: The lung is highly vulnerable during sepsis, yet its functional deterioration accompanied by disturbances in the pulmonary microcirculation is poorly understood. This study aimed to investigate how the pulmonary microcirculation is distorted in sepsis-induced acute lung injury (ALI) and reveal the underlying cellular pathophysiologic mechanism.Using a custom-made intravital lung microscopic imaging system in a murine model of sepsis-induced ALI, we achieved direct real-time visualisation of the pulmonary micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
142
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(162 citation statements)
references
References 45 publications
7
142
0
Order By: Relevance
“…(13) It is demonstrated that the size of the needle used in the CLP procedure can be in uential in different septic outcomes such as mortality, cytokines concentrations, apoptosis, lactic acidosis, and autophagy. Previous studies showed that G-18 and G-21 induced sepsis more e ciently compared to other gauge groups (6,11,12).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…(13) It is demonstrated that the size of the needle used in the CLP procedure can be in uential in different septic outcomes such as mortality, cytokines concentrations, apoptosis, lactic acidosis, and autophagy. Previous studies showed that G-18 and G-21 induced sepsis more e ciently compared to other gauge groups (6,11,12).…”
Section: Introductionmentioning
confidence: 93%
“…Pulmonary complications of sepsis develop as a result of the cumulative effect of circulating cellular elements, soluble in ammatory mediators, and cytokines on the pulmonary tissues. (6) The main underlying mechanism of lung injury during sepsis is demonstrated to be acute alveolar in ltration and changes in respiration ratio (7).…”
Section: Introductionmentioning
confidence: 99%
“…Vacuum suction stabilized lung windows are now widely used to analyze the pulmonary immune system (Looney et al, 2011). This includes neutrophil margination (Kuebler et al, 1994(Kuebler et al, , 1997Park et al, 2019) or immune cell -tumor cell interactions (Hanna et al, 2016), as well as infections of the lung (Sewald, 2018;Ueki et al, 2018).…”
Section: Intravital Microscopy Of the Lung -From Early Beginnings To mentioning
confidence: 99%
“…In recent years, this limitation has been overcome by e.g., combinations of fluorescent dyes and antibodies to differentiate leukocyte subsets. To address the role of neutrophils in a model of sepsis-induced lung injury, Park et al (2019) labeled erythrocytes ex vivo with DiD and reinfused them via a catheter. Concomitantly, vessels were visualized with FITC and Tetramethylrhodamine (TMR) conjugated dextran and neutrophils were specifically labeled in vivo with an anti-Ly6G + monoclonal antibody tagged with a fluorophore.…”
Section: Intravital Microscopy For Analysis Of Alveolar Perfusion Gamentioning
confidence: 99%
“…[6][7][8] In animal models, the depletion of neutrophils reduces the severity of lung injury. 9 A promising therapeutic target would be to inhibit neutrophil recruitment, rather than eliminating them, in ALI. 4 In ARDS, chemokine levels are elevated in the lungs and correlate with outcome.…”
Section: Introductionmentioning
confidence: 99%